ANALISIS PENGARUH PERBANDINGAN DIAMETER MINOR DAN MAYOR ELIPS TERHADAP NILAI KOEFISIEN DRAG MENGGUNAKAN PROGRAM CFD - Afdhal Kurniawan Mainil; Fauzan Andreas; Helmizar (Jurnal Teknik Mesin, 2012)
The rapid development of science and technology to inspire people to create something useful for human life itself. One example is the use of a cylindrical body which can be found on the heat exchanger (heat exchanger) is on shell and tube, chimney, and support offshore platforms. In this case, to obtain an optimum value as well as building construction and minimal ideal would be a mistake, it is necessary to know the characteristics of flow through the body. One of the characteristics of the flow is fluid flow through the cylinder body. Fluid passing through a cylindrical body will result in drag force. Research on the external flow across a body has done much to reduce the drag force. One was to replace the cylinder body with an elliptical geometry. In the present study will be conducted using the CFD numerical model with a test that is circular and elliptical cylinders. In the test model ellipse major and minor diameter ratio is varied (50mm/100mm, 50mm/120mm, 50mm/150mm, 50mm/180mm). In each test model will be calculated the value of the coefficient of drag is happening. The results of the simulations is the use of an elliptical body geometry can reduce the value of the coefficient of drag (CD) of 0.2519 on the minor and major diameter ratio (a/b = 50mm/150mm) than the circular cylinder with a drag coefficient (CD) of 0.5485 and the ratio of diameter minor and major of the most effective to reduce the coefficient of drag on the ellipse is (a/b = 50mm/150mm) than the minor and major diameter ratio (a/b = 50mm/100mm), (a/b = 50mm/120mm), (a/b = 50mm/180mm).